The Lateralized Brain The Neuroscience and Evolution of Hemispheric Asymmetries - Ocklenburg, Sebastian; Ocklenburg, Sebastian; Gunturkun, Onur (Elsevier Science, 2017)
The Lateralized Brain: The Neuroscience and Evolution of Hemispheric Asymmetries is an up-to-date teaching resource for neuroscience faculty members that teach courses concerning hemispheric asymmetries. The book provides students with all relevant information on the subject, while also giving aspiring researchers in the field an up-to-date overview of relevant, previous work. It is ideal for courses on hemispheric asymmetries, that is, the functional or structural differences between the left and the right hemispheres of the brain, and also highlights how the widespread use of modern neuroimaging techniques, such as fMRI and DTI has completely changed the way hemispheric asymmetries are currently investigated. Includes references to key articles, books, protocols and online resources for additional, detailed study Presents classic studies that helped define the field Covers key concepts and methods that are explained in separate call out boxes for quick overview Provides introductory short stories (e.g. classic clinical cases) as a starting point for each chapter